Factors Influencing Organizational Commitment - Fenina Siagian, Nina; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
This study aims to analyze the influence of work motivation, work environment, work discipline, and job satisfaction on employee commitment at PT. BPJS Ketenagakerjaan, Lhokseumawe and Medan Raya Branch Offices. The research employed a quantitative method with saturated sampling, involving 80 permanent employees as respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that work motivation and job satisfaction have a positive and significant effect on employee commitment, while the work environment has a positive effect on job satisfaction but an insignificant effect on employee commitment. The study concludes that improving job satisfaction can enhance employee commitment, and job satisfaction acts as a significant mediating variable in the relationship between the work environment and employee commitment.